Evaluation of HOMA IR in perimenopause patients with abnormal uterine bleeding - Sima, Aneta; Simeonova krstevska, Slagjana; Dabeski, Drage; Livrinova, Vesna (MSD Publications India Pvt Ltd., 2024)
Introduction: Perimenopause as a clinical entity is characterized by a series of symptoms that occur due to estrogen deficiency in multiple organs and systems. Obesity is a risk factor that favors all these changes, especially hyperplasia. Glucose homeostasis is often impaired in these patients, insulin levels are increased, and HOMA IR is increased. Goals: to detect hyperplasia in obese perimenopausal patients with abnormal uterine bleeding to determine insulin levels, HOMA IR, to determine the association between hyperplasia and HOMA IR. Material and Methods: This was a prospective cohort study, performed at the OB/GYN Clinic, over 1 year. 100 patients with abnormal uterine bleeding during the perimenopause were involved, aged 45–50, divided into two groups based on BMI. 1-patients with a BMI above 30, 2-patients with a BMI under 30, and the control group consisted of 40 asymptomatic patients. Results: The average value of glycemia in the first group was higher and was 5.7 mmol/l, the cut-off value was 5,5. The average value of the HOMA-IR insulin resistance index in the first group was highest - 2.8 (the cut-off value was 1.8). Endometrial hyperplasia was registered in the first group at 40.9%. Discussion: The first group registered a significant association between HOMA IR and hyperplasia, the risk of endometrial hyperplasia occurring was eight times higher. The first group registered a significant association between glycemia and endometrial hyperplasia. High levels of glycemia increase the risk of endometrial hyperplasia occurring three times. Conclusion: In menopausal transition patients with abnormal uterine bleeding there is an increased incidence of endometrial hyperplasia, hyperglycemia, and increased HOMA IR. There is a strong association between these changes and the risk of cardiovascular disease increases. Menopause is a period in a woman’s life that requires a multidisciplinary approach to diagnostics and treatment. Keywords: HOMA IR, perimenopause, abnormal bleeding, hyperplasia.